2008
DOI: 10.1158/1078-0432.ccr-08-1199
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms of microRNA Machinery Genes Modify the Risk of Renal Cell Carcinoma

Abstract: Purpose: MicroRNAs (miRNA) are a class of small noncoding RNA molecules that have been implicated in a wide variety of basic cellular functions through posttranscriptional regulations on their target genes. Compelling evidence has shown that miRNAs are involved in cancer initiation and progression. We hypothesized that genetic variations of the miRNA machinery genes could be associated with the risk of renal cell carcinoma. Experimental Design: We genotyped 40 single nucleotide polymorphisms (SNP) from 11 miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
175
2
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(186 citation statements)
references
References 29 publications
5
175
2
4
Order By: Relevance
“…This class of polymorphisms within microRNA binding sites, as well as in microRNAs or their precursors, is emerging as a key risk factor for disease phenotypes (32,33). Shen et al (34) recently reported that a G→C single-nucleotide polymorphism (rs2910164) located within the miR-146a precursor leads to a change from a G:U pair to a C:U mismatch in its stem region and that breast cancer patients who had at least one miR-146a variant C allele were diagnosed with the disease at an earlier age than those without this variant allele (median age, 45 versus 56 years; P = 0.029).…”
Section: Discussionmentioning
confidence: 99%
“…This class of polymorphisms within microRNA binding sites, as well as in microRNAs or their precursors, is emerging as a key risk factor for disease phenotypes (32,33). Shen et al (34) recently reported that a G→C single-nucleotide polymorphism (rs2910164) located within the miR-146a precursor leads to a change from a G:U pair to a C:U mismatch in its stem region and that breast cancer patients who had at least one miR-146a variant C allele were diagnosed with the disease at an earlier age than those without this variant allele (median age, 45 versus 56 years; P = 0.029).…”
Section: Discussionmentioning
confidence: 99%
“…Thirty studies were excluded by article review, including 17 studies repeated or overlapped in the PubMed and Embase databases; 6 studies were not concerned with cancer risk research, 1 study was an animal study, 1 study was a cell study, and 5 studies were meta-analysis. During the reading of the 25 full-text manuscripts, 4 studies were excluded due to incomplete rs11614913 polymorphism distribution data required for OR calculation (10)(11)(12)(13). For the remaining 21 records, baseline characteristics of the patients and control subjects were summarized, the study quality was assessed, HWE in particular was assessed by Chi-square test; two records involving Indian populations published in 2011 were excluded for disagreement with HWE (P<0.05) (14,15), thus leaving 19 articles identified with criteria for inclusion and exclusion (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…As a class of 22-nucleotide noncoding RNAs, miRNAs are thought to function as negative regulators of gene expression. Various single nucleotide polymorphisms (SNPs) exist in miRNA genes that can lead to variations in the quantity of miRNAs, resulting in diverse functional consequences that include cancer development (Horikawa et al, 2008). For example, a study by Zhang et al (2010) provided evidence that an miR-196a2 polymorphism might contribute to CRC susceptibility in Chinese populations through modulating mature miR-196a expression.…”
Section: Introductionmentioning
confidence: 99%